Analisis Yuridis Pengalihan Status Kepemilikan dan Pengelolaan Pelabuhan dari Pemerintah Pusat ke Pemerintah Provinsi (Studi Kasus Pada Pelabuhan Dawi-Dawi Kabupaten Kolaka) - Syamsul Rijal; Ananda, Adhe Ismail (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to analyze port management authority after its delegation from the central government to regional government, and to examine its legal implications on the management and development of Dawi-Dawi Port in Southeast Sulawesi. The research uses a normative-empirical approach by examining statutory regulations and their implementation in practice. The findings indicate that although the transfer of authority is normatively regulated by Law Number 23 of 2014, its implementation faces structural, administrative, and normative obstacles. The incomplete process of asset and personnel transfer, the disharmony of sectoral regulations, and institutional resistance have resulted in a duality of authority between central and regional governments. The implications include not only inefficiency in port governance and development but also legal uncertainty that may harm the public and weaken regional administrative performance. This research recommends regulatory harmonization, institutional restructuring, and acceleration of authority transfer procedures based on legal certainty and service effectiveness.